Disastrous Mechanism of Water Burst by Karst Roof Channel in Rocky Desertification Mining Area in Southwest China - Jie Suo; Qirong Qin; Wenqiang Wang; Zhenhua Li; Cunhan Huang; Youlin Xu; Zuguo Chen (Geofluids)
With the development of coal mining in rocky desertification mining area in Southwest China, water burst is becoming an important disaster in coal mine. In order to grasp the evolution characteristics of water gushing channels in coal mining in rocky desertification mining area, the 1402 working face in Xintian Coal Mine is taken as the research object, and the occurrence of aquifers on the roof of the working face is analyzed, and the water filling path of the aquifers is explored. Besides, the evolution characteristics of water passage in coal seam mining are comprehensively analyzed, by the methods of physical similarity simulation, numerical simulation, and microseismic monitoring. The results show that the key water resource is the atmospheric precipitation, which enters the mine through the original karst fissure and mining-induced fissure. With the continuous advance of working face, the fracture height of overburden increases gradually. Specifically, when the advancement distance of working face exceeds 135 m, the water-conducting cracks in the overlying strata develop to the bottom boundary of the Yulongshan limestone aquifer, and then, the mining-induced fracture and aquifer are conducted; when the working face advances 190 m, the overall overburden mining fissure is divided into fissure opening zone and fissure closed zone. Meanwhile, most of the microseismic events occur in the middle part of the karst roof, and the maximum height of microseismic event is 40 m away from the bottom boundary of the Yulongshan limestone, during the advancing process of the working face. When the mining fissure is connected with the original karst fissure, atmospheric precipitation enters the aquifer through the original karst fissure and enters the gob of working face through the mining fissure. The research results provide the references for prediction and prevention for the water burst disaster in rocky desertification mining area in Southwest China.